Wspieranie potencjału psychospołecznego młodzieży na przykładzie projektu me_HeLi-D - Borzucka-Sitkiewicz, Katarzyna; Kowalczewska-Grabowska, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
W artykule zaprezentowano projekt “Mental Health Literacy and Diversity. Enhancing Mental Health and Resilience through digital Resources for Youth” (me_HeLi-D), który jest realizowany w ramach programu Erasmus+ w partnerstwie międzynarodowym. Projekt jest zorientowany na bezpośrednią poprawę zdrowia psychicznego i budowanie niezbędnych umiejętności w tym zakresie, a także na promowanie świadomości różnorodności wśród uczniów. Jego nadrzędnym celem jest opracowanie opartego na badaniach, ogólnie dostępnego narzędzia cyfrowego, przeznaczonego dla konkretnej grupy docelowej jaką są uczniowie (w wieku od 12 do 15 lat). Narzędzie ma służyć uczniom do wspierania ich zasobów osobistych oraz wzmacniania i szerzenia wiedzy na temat zdrowia psychicznego.

The project presented during the conference is called “Mental Health Literacy and Diversity. Enhancing Mental Health and Resilience through digital Resources for Youth” (me_HeLi-D). The project is implemented under the Erasmus+ program in international partnership. It is focused on directly improving mental health and building mental health skills, and more indirectly, promoting diversity awareness among students. The aim of the project is to develop a research-based digital tool, publicly available, for a specific target group of students (aged 12 to 15). The tool is intended to serve students in supporting their personal resources, strengthening and spreading knowledge about mental health. The project consortium includes professionally active teachers, health psychologists and clinical psychologists, as well as scientists dealing with inclusive education, pedagogy, psychology, sociology and computer science.
Supporting the psychosocial potential of young people based on the me_HeLi-D project
Keywords: zdrowie psychospołeczne; młodzież; narzędzia cyfrowe; dobrostan; psychosocial health; youth; digital tools; well-being